MODEL BIAYA TIDAK LANGSUNG PROYEK STRUKTUR GEDUNG BETON BERTULANG - Nudja S, I Ketut; Sutarja, I N.; Nadiasa, Mayun (JURNAL SPEKTRAN; Vol. 2, No.2, Juli 2014, 2014)
The cost of the project itself , in line with the accounting system which consists of direct costs and indirect costs . Contractor in determining competitive bidding strategy, should propose a cost which include estimate real cost plus mark up . Based on observations at PT. Sarana Bangun Ragam Cipta, a contractor company , found that the company does not  follow the rules mentioned above, Besides that the book keeping system for the project cost has not implemented a financial accounting system properly , so that the  proportion of direct costs and indirect costs of each project is un know. It required a study to be conducted to  determine the proportion of direct costs to indirect costs and indirect cost model. Quantitative research was conducted on the 12 (twelve ) project of  reinforced concrete building structures using two (2 ) independent variables , namely the direct costs ( X 1 ) and duration ( X 2 ) and 1 ( one ) dependent variable , ie indirect costs (? ) . Descriptive analysis to determine the proportion of indirect costs to direct costs . Analysis of data using multiple linear regression analysis to determine the indirect cost model of reinforced concrete building structures projects. From analysis found the average proportion of indirect costs to direct cost was 8.50 % , meanwhile  indirect cost model is ? = - 1.462E7 + 0.056 ( X 1 ) + 558,775.937 ( X 2 ) , where : ? = Indirect costs ( Rp . ) , X 1 = direct costs (Rp .) , X 2 = Duration ( days ) . The proportion of indirect costs can be used to calculate indirect costs = 0.085 x direct costs and the above model can also be used to predict the value of ? with accuracy 90% or at ? (±) 0.10, if the values ??of X 1 and X 2 is know on popolation where the data is taken
Keywords: Model , indirect costs , construction projects , buildings , reinforced concrete , direct costs , duration.